The Intensive Monitoring Group and Youth Justice - Evans, Keith Barrie (Auckland University of Technology, 2012)
The IMG is one of several new initiatives for dealing with youth offending in New Zealand designed and administered by the Youth Courts. Other initiatives include the Christchurch Drug Court and the Marae Youth Monitoring Court at Poko-o-Rawiri Marae in Gisborne. Established in 2007, the IMG seeks to reduce youth offender recidivism by targeting the small number of youth offenders [about five per cent (Lovell and Norris, 1990; Moffit, 1993) responsible for the greater number of crimes. The intervention addresses the underlying issues described by Judge Becroft as creating a significant overlap between risk factors for offending, background of family dysfunction and disadvantage, psychological disorders such as conduct disorder and learning disabilities, and drug/alcohol dependence/addiction (Becroft, 2009,McLaren, 2000). This study asked the research question ‘what are the key features of the IMG that enhance the rehabilitation of youth offenders and reduce recidivism?’ To address this question the thesis located the IMG ntervention within the theoretical framework of therapeutic jurisprudence (Winick and Wexler, 2003) whereby court sanctions are used not simply to punish but to effect behaviour change (Walker, 2001). Using a combination of phenomenology methodology and case studies the research sought to develop a more holistic understanding of the experiences of the key actors in the IMG (Polit and Hungler, 1995), and identify the key features of the IMG intervention that make it effective in reducing youth offender recidivism. The case studies in this thesis indicated that the IMG intervention reduced the chances of the youth offenders re-offending. The key to the effectiveness of the intervention is the dedicated team of professionals working intensively with the youth offenders, providing coordinated services that address the individual needs of the youth offender, on-going regular monitoring that is supportive but holds the youth offender accountable, thus actively engaging them in their rehabilitation. However, the IMG faces a number of challenges, such as the limitation of resources which makes it difficult to extend the intervention to larger groups of youth offenders, lack of understanding of the role and functions of the IMG both by the general public that seems to take a retributive rather than rehabilitative position with regards to youth offenders, and even within significant government departments that work with youth offenders. There is also the challenge of creating post-IMG opportunities for the IMG graduates to move into, such as employment, training and on-going mentoring so that they do not go back to the environment of dysfunction and crime. These challenges are examined and some recommendations provided as to how the IMG intervention could be enhanced.
Keywords: Young offenders; Intervention; Intensive monitoring group; Youth courts